2017
DOI: 10.1128/aem.03330-16
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gluten Degradation and Oral Microbial Profiles in Healthy Individuals and Celiac Disease Patients

Abstract: Celiac disease (CD) is a chronic immune-mediated enteropathy induced by dietary gluten in genetically predisposed individuals. Saliva harbors the second highest bacterial load of the gastrointestinal (GI) tract after the colon. We hypothesized that enzymes produced by oral bacteria may be involved in gluten processing in the intestine and susceptibility to celiac disease. The aim of this study was to investigate salivary enzymatic activities and oral microbial profiles in healthy subjects versus patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…In faecal samples, CeD showed significant enrichment of ASVs affiliated to genus Lactobacillus in comparison to FDR and DC. This is in line with previous study in which, higher abundance of Lactobacillus was observed in oral microbiome of patients with CeD (Tian et al, 2017). Moreover, there are reports stating that the certain Lactobacillus species degrade gliadin and increases the availability of antigenic peptides (Engstrom et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…In faecal samples, CeD showed significant enrichment of ASVs affiliated to genus Lactobacillus in comparison to FDR and DC. This is in line with previous study in which, higher abundance of Lactobacillus was observed in oral microbiome of patients with CeD (Tian et al, 2017). Moreover, there are reports stating that the certain Lactobacillus species degrade gliadin and increases the availability of antigenic peptides (Engstrom et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…This disorder is characterized by typical histological jejunal lesions showing total or subtotal villous atrophy, crypt hyperplasia and lymphocyte infiltration, which results in malabsorption of most nutrients in the small intestine [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, 3 out of 4 couples in this study exhibited highly similar phage communities. The dissimilar couple may be due to celiac disease diagnosed in one of the partners, which is known to alter oral ecology (58). These results suggest that genetics and cohabitation do not significantly impact a person’s oral phage community.…”
Section: Resultsmentioning
confidence: 99%